Ba/Ca, Mg/Ca, and stable isotope values since the LGM measured in individual and bulk shells of planktic foraminifera from four cores of the equatorial Pacific - Fritz-Endres, Theresa (PANGAEA, 2022)
The datasets compile Ba/Ca (µmol/mol), Mg/Ca (mmol/mol), δ18O (VPDB, ‰), and δ13C (VPDB, ‰) measured in individual and bulk shells of spinose planktic foraminifera Trilobatus sacculifer and non-spinose planktic foraminifera Neogloboquadrina dutertrei and Pulleniatina obliquiloculata collected from two cores on the Ontong Java Plateau (OJP) and two cores from the Eastern Equatorial Pacific (EEP). Trace elements in individual shells are measured with a laser ablation inductively coupled plasma mass spectrometer (ICP-MS) and trace elements in bulk shells are measured with a solution ICP-MS. Stable isotope analysis is conducted on paired individual shells (paired based on Mg/Ca content) with an isotope ratio mass spectrometer. ID denotes which individual shells are paired for the analysis.
Keywords: Ba/Ca; equatorial Pacific; LGM; Mg/Ca; paleoproductivity; planktic foraminifera; Stable isotopes